IDENTITY CONSTRUCTION AND CULTURAL VALUES IN THE SCREENPLAY OF ZATHURA: A SPACE ADVENTURE (2005) - Aidelwaiss Ulfatul Kamilah; Arsyi Azwar; Jasmine Flora Nirwana (Saksama: Jurnal Sastra, 2026)
This study examines Zathura: A Space Adventure (2005), based on the screenplay by David Koepp, as a work of popular literature that grounds a fantastical cosmic journey in the "quotidian realities" of a fragmented family. By analyzing the script's portrayal of sibling rivalry and the logistical stresses of a "three-day Dad week," the research explores how fantasy serves as a vehicle for identity negotiation. Utilizing Joseph Campbell’s Hero’s Journey framework, the narrative is traced from the "Departure" in a cemetery to the "Initiation" through trials—such as the attack of a "defective robot"—culminating in a "Return with Change" where the house is "perfectly restored" and the brothers are psychologically transformed. Stuart Hall’s Cultural Identity Theory is applied to analyze how Walter and Danny move beyond fixed labels of "baby" and "older brother" to negotiate a new, unified identity through shared crisis. The script transmits core cultural values—empathy, responsibility, and solidarity—exemplified in domestic scenes like Walter’s attempt to cook "macaroni and cheese" for Danny while adrift in space. Ultimately, the analysis demonstrates that Zathura transcends its sci-fi spectacle to function as a cultural artifact that facilitates critical reflection on family connection and the "journey home" toward emotional maturity.